An insilico study to identify possible novel mitogen activated protein kinases signalling pathway inhibitors from Selected natural antioxidants. - SUBA MALANI. S; SASI KUMAR.A (International Journal of Pharma and Bio Sciences, 2017)
Prolonged exposure to stress induces changes in various neural circuits of different brain regions that alter the balances in neuronal activities involving microglial activation, signalling pathways and cellular homeostasis by antioxidants. Sustained and extended activation of Mitogen activated protein kinases (MAPK) signalling cascades, release proinflammatory cytokines leads to neuroinflammation and neurodegeneration. As various phosphorylated MAPK subfamilies such as P38MAPK, c-Jun N terminal kinase (JNK), Extracellular receptor kinases (ERK) ½ and ERK5 are known to be involved in this pathway and the inhibitors of the pathway become the targets for developing efficient drugs in the drug discovery field. In the current study, the antioxidants of natural origin present in the plants namely α asarone, Quercertin, Diosmetin, Resveratrol, Glabridin, were used to identify efficient inhibitor against MAPK’s pathways. In this study, an insilico approach was done to analyse the drug like properties of the ligands. DruliTo and ADMET Sar softwares were employed in the analysis of the following profiles- Blood brain barrier permeability, Human intestinal absorption, toxicity profile and LD50 values. Molecular docking was done by iGEMDOCK software. The results of IGEMDOCK shows that except Resveratrol all other four ligands namely α asarone, Quercertin, Diosmetin, Glabridin has got lower binding energy, good ADMET sar profile and also all the drugs obey’s the lipinski’s rule. The result of this study indicates that the antioxidant extracts of α asarone, Quercertin, Diosmetin, Glabridin can be tried as a novel inhibitor of MAPK signalling pathways. Further in vivo and in vitro studies are necessary to validate and implement these drugs in clinical trials.